The implementation of content-based instruction in english as a second language class / Nurul Aini Abdullah @ Radhika Balakrishnan - Abdullah, Nurul Aini (2011)
The study was aimed at ascertaining the degree of effectiveness of the Content Based Instruction (CBI) in a Malaysian ESL classroom. It was also aimed at identifying the teachers’ response in relation to the implementation of CBI in their ESL classroom. This study was conducted in SMK Pusa Sarawak on a group of 47 ESL students from three science stream classes while the other 40 students of the control group is from one art stream class. It was carried out for a period of 2 months from the months of June to July.The research employed a mixed-method approach whereby both the quantitative and qualitative means of data collection are incorporated into the research. The research design was a quasi-experimental approach engaging an experimental and a control group of students. The quantitative data were obtained through administration of questionnaire as well as language test. The qualitative data were gathered through semi-structured interviews with the teachers. The CBI approach was used to teach English to the selected students in the experimental group. The findings reveal that the teachers are not quite familiar with the CBI method and related that they viewed it as an effective way of teaching English. The most revealing aspect of the findings was the significant difference in terms of improvement using the Pearson Significance Two-tailed test between the pretest and posttest of the experimental group. This implies that CBI is to some extent effective in improving the students' language skills.